2011
DOI: 10.1016/j.jnoncrysol.2011.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and crystallization behavior of TiO2 doped ZBLAN glasses

Abstract: ZBLAN glasses with the composition (in mol%) of (100 − x)(53 ZrF 4 +19 BaF 2 + 5LaF 3 +3AlF 3 +20NaF)+xTiO 2 (x = 0, 1.0 and 2.0 mol%) were prepared using a conventional melting technique in dry nitrogen atmosphere. The thermal stability, glass-forming ability, and crystallization kinetics of the ZBLAN system as a function of the TiO 2 concentrations were investigated by Differential Scanning Calorimetry (DSC). Also, the crystalline phases were determined by X-ray Diffraction (XRD). Our study indicates that ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Compared with AYF and ZBLAN [15] which did not have TeO 2 , these fluoroaluminatetellurite glasses had larger DT, S and c. At the same time, these three criterions agreed well with each other and it could be inferred that a suitable ratio of TeO 2 could improve vitrification ability of fluoroaluminate glass greatly. Table 1 Characteristic temperatures (T g , T x , T p , T m ) and DT, S, c of present glasses.…”
Section: Glass Forming Abilitysupporting
confidence: 52%
See 4 more Smart Citations
“…Compared with AYF and ZBLAN [15] which did not have TeO 2 , these fluoroaluminatetellurite glasses had larger DT, S and c. At the same time, these three criterions agreed well with each other and it could be inferred that a suitable ratio of TeO 2 could improve vitrification ability of fluoroaluminate glass greatly. Table 1 Characteristic temperatures (T g , T x , T p , T m ) and DT, S, c of present glasses.…”
Section: Glass Forming Abilitysupporting
confidence: 52%
“…Some Te-O bonds could have been replaced by the Te-F bonds, and this indicated that weaker bonds are introduced into the system. For the concentration of TeO 2 , a notable change in T g was observed, and the change could be due to the higher average bond energy (the Te-O covalent bonds) [15].…”
Section: Glass Forming Abilitymentioning
confidence: 95%
See 3 more Smart Citations